Health and nutrition status of farm women in rural India: Case of Indo-Gangetic plains - JOSHI, PRATIBHA; SHARMA, J P; SHARMA, NISHI; SINGH, B K; AHMAD, NAFEES; GILLS, RESHMA (The Indian Journal of Agricultural Sciences, 2018)
Women in India are facing several health-related issues, which ultimately affect the economic output of the nation. The health of Indian women is intrinsically linked to their status in society. Haryana and Uttar Pradesh are some of the few states in India which belong to Indo-Gangetic Plains where an overwhelming number of rural women have always been a part of the active work force in agriculture, forest protection, cattle care, and dairying. Present study is an attempt to know the food consumption and dietary intakes of farm women in rural sector of the UP and Haryana. Collected data were analyzed with the help of suitable statistical techniques. Education, energy consumption and protein consumption have significantly positive relationship with nutritional status of respondents, whereas family size has significantly negative relationship with nutritional status. It was found that the diets were inadequate in energy, protein, iron, Î²-carotene and ascorbic acid contents to the tune of 16.71 and 15.91; 7 and 10.58; 14.33 and 21.63; 25.66 and 34.33; 16.71 and 18.05 percent, respectively in selected villages of Haryana and Uttar Pradesh. These comparisons were made with recommended dietary allowances (ICMR 2010). Iron intake in the daily diet of women in both villages was found to be 19.7 mg and 20.54 mg, which is 34.33 and 31.53 per cent less than recommended level (30 mg). Prevalence of Chronic Energy Deficiency (CED) was found to be higher among the farm women of both the states.